MAMI: a birth cohort focused on maternal-infant microbiota during early life - Izaskun García-Mantrana; Cristina Alcántara; Marta Selma-Royo; Alba Boix-Amorós; Majda Dzidic; Jose Gimeno-Alcañiz; Isabel Úbeda-Sansano; Ignacio Sorribes-Monrabal; Ramón Escuriet; Fernando Gil-Raga; Anna Parra-Llorca; Cecilia Martínez-Costa; et al. (BMC, 2019)
Abstract Background Early microbial colonization is a relevant aspect in human health. Altered microbial colonization patterns have been linked to an increased risk of non-communicable diseases (NCDs). Advances in understanding host-microbe interactions highlight the pivotal role of maternal microbiota on infant health programming. This birth cohort is aimed to characterize the maternal microbes transferred to neonates during the first 1000 days of life, as well as to identify the potential host and environmental factors, such as gestational age, mode of delivery, maternal/infant diet, and exposure to antibiotics, which affect early microbial colonization. Methods MAMI is a prospective mother-infant birth cohort in the Spanish-Mediterranean area. Mothers were enrolled at the end of pregnancy and families were follow-up during the first years of life. Maternal-infant biological samples were collected at several time points from birth to 24 months of life. Clinical and anthropometric characteristics and dietary information is available. Specific qPCR and 16S rRNA gene sequencing as well as short chain fatty acid (SCFAs) profile would be obtained. Multivariable models will be used to identy associations between microbiota and clinical and anthropometric data controlling for confounders. MAMI would contribute to a better understanding of the interaction between diet, microbiota and host response in early life health programming, enabling new applications in the field of personalized nutrition and medicine. Trial registration The study is registered on the ClinicalTrial.gov platform NCT03552939. (June 12, 2018).